Communication and media studies in South Africa: Observations, impressions and remarks. (1st March 2013) - Salawu, Abiodun
This article offers some self-reflexive comments on Communication and media studies in South Africa. The discipline in South Africa, presents a very exciting and intriguing posture for the simple fact that it allows for diversity– observable in the variety of labels, emphases and curricula. Equally enviable is the currency of some aspects of the programmes offered in the country and the strong theoretical foundation of research publications. Yet some deficiencies observed in a number of the curricula provoke a call for standardization of programmes offered by the various universities. The lack of regulation could be held responsible for some lapses noticeable in the structure of the various programmes. Drawing on observations of South Africa's communication and media education landscape, this article argues that the field seems to be withdrawn and too inward-looking that is evidenced by the lack of interest in the affairs of the African Council for Communication Education (ACCE) and what used to be the predominantly locally oriented content of South African journals. Thus, South African academia is tactically excluded from the leadership which it should provide on the African continent. Some cross-references are made to the situation in Nigeria, being the country where the writer had been involved in communication and media scholarship before moving to South Africa.